Optimizing Ram Testing Method For Test Time Saving Using Automatic Test Equipment - Kesavan Prabagaran, Premkumar (2017)
Due to the memory size increase drastically in the field programable gate array (FPGA) or system on chip (SOC) device, it become hard to meet the tests cost budget of the product especial for low-cost device. One of the major factor of test cost contributed is the test time. For the low-cost product, the tolerance number of the defects per million (DPM) are relative high compare to high cost product. By taking this advantage, an optimizing memory testing method able to implement to minimize the test time without jeopardize the test coverage. A memory Build-in Self-test (BIST) design with capability of algorithm failing sequence capture have been developed to implement in the Automate Test Equipment (ATE) flow for production screen. 3 selected algorithm have been tested on the 8 detect units in ATE flow to prove the concept of this method. The failing algorithm sequence of the units have been logged into database and analyzed for algorithm trimming. With the proper examples, the algorithm trimming location and test time saving calculation have been shown in this research. For this examples, approximate 33% of test time reduction observed for 1Kbyte memory testing with Hammer Head algorithm. In summary, this research has proposed the memory test time saving by optimizing the tests algorithm on the ATE flow.